2021
DOI: 10.1098/rspb.2021.1931
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of parental contributions to the behavioural tolerance of elevated pCO2in a coral reef fish

Abstract: Knowledge of adaptive potential is crucial to predicting the impacts of ocean acidification (OA) on marine organisms. In the spiny damselfish, Acanthochromis polyacanthus , individual variation in behavioural tolerance to elevated pCO 2 has been observed and is associated with offspring gene expression patterns in the brain. However, the maternal and paternal contributions of this variation are unknown. To investigate parental influence of behavioural pCO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 77 publications
3
16
0
Order By: Relevance
“…84 This last study proposed the use of cytochrome P450 1A gene (cyp1a) as a biomarker for monitoring BPA pollution. Further, and in line with previous research investigating the impacts of elevated pCO 2 on the brain transcriptome of coral reef fishes, [97][98][99] Schunter et al…”
Section: Insights From Comparative Transcriptomicssupporting
confidence: 84%
See 1 more Smart Citation
“…84 This last study proposed the use of cytochrome P450 1A gene (cyp1a) as a biomarker for monitoring BPA pollution. Further, and in line with previous research investigating the impacts of elevated pCO 2 on the brain transcriptome of coral reef fishes, [97][98][99] Schunter et al…”
Section: Insights From Comparative Transcriptomicssupporting
confidence: 84%
“…To date, most research investigating physiological and behavioral changes of coral reef fish under warming and ocean acidification conditions has focused on transcriptomic and epigenetic modifications. 97,[99][100][101][102][103][104][105] Transcriptomic expression alone, however, is not sufficient to reflect protein levels and to therefore explain genotype-phenotype relationships. 106 Measuring the presence and abundance of proteins is thus indispensable for the complete understanding of biological processes and cellular phenotypes, especially since post-translational modifications inferred from proteomics have been shown to be more strongly correlated to phenotypic observations than those from transcriptomics [106][107][108] (Figure 1).…”
Section: The Rise Of Proteomicsmentioning
confidence: 99%
“…CC-BY-NC-ND 4.0 International license perpetuity. It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted September 19, 2022. ; https://doi.org/10.1101/2022.09.18.508416 doi: bioRxiv preprint response to elevated CO2 in the brain and gills of fish (Heuer & Grosell, 2014;Kang et al, 2022;Mittermayer et al, 2019;Monroe et al, 2021) suggesting that high CO2 levels affect the expression and activity of CA. Additionally, transcripts encoding potassium channel transporters, and a Na + /K + transporting ATPase were DE in the gobies.…”
Section: Discussionmentioning
confidence: 99%
“…Carbonic anhydrase (CA), an enzyme which plays a key role in CO 2 excretion, acid-base balance, and ion-regulation was upregulated in gobies from the CO 2 seep, which could facilitate increased CO 2 excretion thereby preventing acidosis and also enhance transport of O 2 to the brain (Rummer & Brauner, 2011). Various other CA isoforms have been identified to be DE in response to elevated CO 2 in the brain and gills of fish (Heuer & Grosell, 2014; Kang et al, 2022; Mittermayer et al, 2019; Monroe et al, 2021) suggesting that high CO 2 levels affect the expression and activity of CA. Additionally, transcripts encoding potassium channel transporters, and a Na + /K + transporting ATPase were DE in the gobies.…”
Section: Discussionmentioning
confidence: 99%
“…Though it is unclear how fish are selected to become brood stock at the Whiteshell Hatchery, it is possible that fish that perform best in the high CO2 conditions of a hatchery setting are also the fish that would be more tolerable to high CO2 and used for breeding (Ellis et al, 2017;. Furthermore, multiple studies looking at marine reef fishes have found that if the parental generations are exposed to high CO2 conditions certain adaptive traits are shared with offspring (Miller et al, 2012;Monroe et al, 2021). It is also possible that a combination of both intergenerational and generational effects are at play when it comes to tolerance of CO2 in fish (Schunter et al, 2018), and future studies should investigate these effects.…”
Section: Discussionmentioning
confidence: 99%